2003
DOI: 10.1046/j.1471-4159.2003.01728.x
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase A and protein kinase C signaling pathway interaction in phenylethanolamine N‐methyltransferase gene regulation

Abstract: The protein kinase A (PKA) and protein kinase C (PKC) signaling pathways appear to interact in regulating phenylethanolamine N-methyltransferase (PNMT) promoter-driven gene transcription in PC12 cells. Forskolin treatment of cells transfected with the rat PNMT promoter-luciferase reporter gene construct pGL3RP893 increased promoter activity approximately two-fold whereas phorbol-12-myristate-13 acetate (PMA) treatment had no effect. However, simultaneous forskolin and PMA treatment synergistically activated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 60 publications
1
34
0
1
Order By: Relevance
“…For example, Lysine-551 is the major forskolin and PMA mediated the proteolytic cleavage of Sp1 thereby suggesting a mechanism by which these inducers activate Sp-dependent transcription. 28 PMA uses a different signaling pathway to induce Sp1. PMA is used to activate the ERK/MAPK kinase pathway.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Lysine-551 is the major forskolin and PMA mediated the proteolytic cleavage of Sp1 thereby suggesting a mechanism by which these inducers activate Sp-dependent transcription. 28 PMA uses a different signaling pathway to induce Sp1. PMA is used to activate the ERK/MAPK kinase pathway.…”
Section: Discussionmentioning
confidence: 99%
“…This new functional aspect becomes critical in pathological conditions in which overexpression of T-type channel enhances the ability of LVA channels to regulate Ca 2+ -entry near resting conditions. In the case of chromaffin cells, expression of ␣1H T-type channels during exposure to cAMP [26], ␤1-adrenergic stimulation [54] and chronic hypoxia [55,56] represents a nice example of how T-type channels recruitment and coupling to exocytosis may generate a positive feedback that mimics the adrenal responses to stress stimuli ("fight-orflight" response) [61,62].…”
Section: Discussionmentioning
confidence: 99%
“…Wild-type (pGLRP893) and nested deletion PNMT promoter-luciferase reporter gene constructs (pGL3RP442, pGL3RP392, and pGL3RP60) were generated as described previously (Ebert et al, 1994;Tai et al, 2001). PNMT promoter-luciferase reporter gene constructs containing mutations of the Ϫ165 bp Egr-1 (pGL3RP-893mutEgr-1) and the Ϫ168 and/or Ϫ48 bp Sp1 (pGL3RP893mutS-p1A, pGL3RP893mutSp1B and pGL3RP893mutSp1A/B) binding sites were generated by site-directed mutagenesis Her et al, 2003;Tai and Wong, 2003). The pRSV-LacZ plasmid containing the ␤-galactosidase gene was used as a normalization control to correct for variable transfection efficiency.…”
Section: Methodsmentioning
confidence: 99%
“…Functional Sp1 binding elements are located at Ϫ48 and Ϫ168 bp in the rat PNMT promoter , and we have shown that the Ϫ48 bp Sp1 site contributes to the cooperative activation of the PNMT promoter by PKA and PKC . Although NGF did not alter Sp1 protein levels in PC-12 cells, Sp1 must be phosphorylated to bind to its consensus element and activate transcription (Kadonaga et al, 1987;Her et al, 2003;Tai and Wong, 2003), and recent findings indicate that NGF does increase Sp1-DNA binding (Liu et al, 2001;Melnikova and Gardner, 2001). The present study showed that site-directed mutation of the Ϫ168-bp Sp1 site attenuated NGF activation of the PNMT promoter, whereas mutation of the Ϫ48 bp Sp1 site or both Sp1 sites eliminated NGF activation.…”
mentioning
confidence: 89%